Factors Associated With Contraceptive Use In Reproductive Age Couples - Desak Nyoman Suryaningrat; Ni Wayan Suniyadewi; Ni Luh Putu Dewi Puspawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Mothers are family members who play an important role in family life. Maternal deaths that occur in every minute at every day are mostly caused by complications related to pregnancy, childbirth, and puerperal. Contraceptive use in reproductive age couples is one of the strategies of the family planning to reduce maternal mortality. This study aimed to investigate the factors associated with contraceptive use in reproductive age couples. This study used a correlational design with a cross-sectional approach. The samples were 56 people selected using a non-probability sampling technique, i.e., purposive sampling.  Data were analyzed using Rank Spearman test and contingency coefficient test. The results showed that there was a correlation between contraceptive use and factors of age, education, employment, customs / culture and quality of family planning services with a p-value of <0.05. This study recommends that Mengwi Public Health Center I provide a counseling room for family planning acceptors and increase the schedule of family planning services as well as improve the quality of health workers especially in giving counseling about contraceptive use.